The Individualization of Foreign Language Teaching in the University-level Professional Education - Muntian, Svitlana; Valentinova, L. К. (My University, 2012)
The article explores the pedagogical conditions facilitating the development of students’ skills of public presentation of their individual creative activity. The creation of conditions is a major strategy to individualize foreign language teaching in the university-level professional education
Keywords: teaching differentiation; presentation; self-directed learning; teaching individualization